2006
DOI: 10.1016/j.cub.2006.01.058
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis MAX Pathway Controls Shoot Branching by Regulating Auxin Transport

Abstract: The MAX-dependent hormone is a novel regulator of auxin transport. Modulation of auxin transport in the stem is sufficient to regulate bud outgrowth, independent of AXR1-mediated auxin signaling. We therefore propose an additional mechanism for long-range signaling by auxin in which bud growth is regulated by competition between auxin sources for auxin transport capacity in the primary stem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
476
1
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 423 publications
(528 citation statements)
references
References 53 publications
(79 reference statements)
36
476
1
6
Order By: Relevance
“…Some studies have demonstrated that in the strigolactone mutants the auxin levels were higher (Beveridge et al 1997b;Bennett et al 2006) whereas others that the mutants and the wild type did not differ (Beveridge et al 1996;Morris et al 2001;Arite et al 2009). There is also support for a role of strigolactones in reducing polar auxin transport both by means of radiolabeled auxins and PIN efflux marker lines, although contradictory results concerning subcellular relocalisation of PINs in root tips have been reported in different experiments and when the root and shoot systems were compared (Beveridge et al 2000;Bennett et al 2006;Lazar and Goodman 2006;Lin et al 2009;Crawford et al 2010;Shinohara et al 2013). Recently, strigolactone action in stems was found to trigger PIN1 depletion from the plasma membrane of xylem parenchyma cells and depended on clathrin-mediated membrane trafficking (Shinohara et al 2013).…”
Section: Strigolactones Increase Primary Root Lengthmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have demonstrated that in the strigolactone mutants the auxin levels were higher (Beveridge et al 1997b;Bennett et al 2006) whereas others that the mutants and the wild type did not differ (Beveridge et al 1996;Morris et al 2001;Arite et al 2009). There is also support for a role of strigolactones in reducing polar auxin transport both by means of radiolabeled auxins and PIN efflux marker lines, although contradictory results concerning subcellular relocalisation of PINs in root tips have been reported in different experiments and when the root and shoot systems were compared (Beveridge et al 2000;Bennett et al 2006;Lazar and Goodman 2006;Lin et al 2009;Crawford et al 2010;Shinohara et al 2013). Recently, strigolactone action in stems was found to trigger PIN1 depletion from the plasma membrane of xylem parenchyma cells and depended on clathrin-mediated membrane trafficking (Shinohara et al 2013).…”
Section: Strigolactones Increase Primary Root Lengthmentioning
confidence: 99%
“…Strigolactones affect auxin fluxes (see above) (Bennett et al 2006;Brewer et al 2009;Crawford et al 2010;Ruyter-Spira et al 2011;Shinohara et al 2013), so it was expected that strigolactones may also have an effect on lateral root formation. Thus far, two reports describe a negative influence of strigolactones on lateral root density in a MAX2-dependent manner (Fig.…”
Section: Strigolactone Regulation Of Lateral Root Formation Depends Omentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the discovery of SMS as a strigolactone, studies with Arabidopsis SMS mutants led to reinterpretation of the theories of Sachs and Bangerth and the establishment of the current auxin transport hypothesis, which proposed that axillary buds compete for limited auxin transport capacity in the main stem (Bennett et al, 2006;. This is based on the premise that in order for an axillary bud to grow it must be able to export auxin and that the main stem of a wild-type plant is saturated with apically derived auxin .…”
mentioning
confidence: 99%